Kajian Online Sistem Informasi BRI (BRINETS): Pendekatan Technology Acceptance Model (TAM) - Wahyu Meiranto (Jurnal Akuntansi Multiparadigma, 2011)
Study of BRI Online Information System (BRINETS): Technology Acceptance Model (TAM) Approach. The purpose of this research is to analyze factors that effecting acceptance and actual use of BRI technology information system (BRINETS) using TAM (Technology Acceptance Model). Two variables of TAM used in this research are perceived ease of use and perceived of usefullness. Samples of the research were BRINETS users at BRI Semarang. There were 70 respondents involved. The data was analyzed by using PLS. The results indicate that experience and complexity have significant effect to perceived ease of use. Furthermore, perceived ease of use significantly affected the attitude toward using technology. Finally, behaviour intention significantly influence the actual use of technology